2015
DOI: 10.1016/j.molcel.2015.05.014
|View full text |Cite
|
Sign up to set email alerts
|

A Phosphosignaling Adaptor Primes the AAA+ Protease ClpXP to Drive Cell Cycle-Regulated Proteolysis

Abstract: SUMMARY The response regulator CpdR couples phosphorylation events in Caulobacter crescentus with the AAA+ protease ClpXP to provide punctuated degradation of crucial substrates involved in cell cycle regulation. CpdR functions like an adaptor to alter substrate choice by ClpXP, however it remains unclear how CpdR influences its multiple targets. Here we show that, unlike canonical ClpXP adaptors, CpdR alone does not strongly bind its substrate. Instead, CpdR binds the N-terminal domain of ClpX and prepares (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 48 publications
(76 citation statements)
references
References 51 publications
1
75
0
Order By: Relevance
“…We found that at least one unidentified factor produced by σ K is required to activate CmpA/ClpXP-mediated degradation of SpoIVA in mutant cells, and that σ K is required for degradation of CmpA in properly sporulating cells. It is possible that the additional factor required for SpoIVA degradation is responsible for a post-translational modification of SpoIVA that marks it as a substrate for degradation by CmpA/ClpXP, or that recruitment of SpoIVA to ClpXP requires a second factor, in addition to CmpA (Lau et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…We found that at least one unidentified factor produced by σ K is required to activate CmpA/ClpXP-mediated degradation of SpoIVA in mutant cells, and that σ K is required for degradation of CmpA in properly sporulating cells. It is possible that the additional factor required for SpoIVA degradation is responsible for a post-translational modification of SpoIVA that marks it as a substrate for degradation by CmpA/ClpXP, or that recruitment of SpoIVA to ClpXP requires a second factor, in addition to CmpA (Lau et al, 2015). …”
Section: Discussionmentioning
confidence: 99%
“…CtrA inactivation is tightly coupled to its degradation by the ClpXP protease that depends on CpdR, an adaptor protein, whose activity also depends on CckA-ChpT [17]. In contrast to CtrA, CpdR is only active when dephosphorylated [17,18]. Thus, under conditions when CtrA is inactivated, it is also targeted for degradation by ClpXP and CpdR.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, localization of the ClpXP protease is not essential for all its activity in vivo as some ClpXP substrates, such as FtsZ, are degraded in swarmer cells when ClpXP is delocalized (130). Finally, recent observations reconstituting protein degradation with purified protein components support a model where CpdR, RcdA and PopA act as biochemical adaptors that coordinate the delivery of a range of substrates, including CtrA, directly to ClpXP protease for destruction during Caulobacter cell cycle (64; 74; 115). More precise roles for each of these adaptors are described below.…”
Section: Cell Cycle Progressionmentioning
confidence: 83%
“…Auxiliary factors called adaptors aid in generating specificity or altering substrate choice for these proteases as required in different bacteria or pathways (for a recent overview see (6)). For example, in E. coli the stationary phase sigma factor RpoS is degraded by the ClpXP protease only in the presence of the RssB adaptor (9; 100; 132) and as will be described in detail below, adaptors play a central role in driving regulated protein degradation during the Caulobacter cell cycle (64; 74). The combination of adaptors and inherent protease specificity provides for rapid yet selective protein degradation in both stress and normal growth conditions (Figure 1).…”
Section: Introductionmentioning
confidence: 99%